A hydrophobic aerogel composite coil and a preparation method thereof
By using a liquid-conducting network layer and a circulating pump to circulate liquid during the preparation process of silica airgel composite materials, the problems of uneven dipping and complex hydrophobic modification processes are solved, and efficient and uniform hydrophobicity is achieved. Modification significantly improves the thermal insulation performance and hydrophobicity of the material.
Patent Information
- Application Number
- CN202211528987.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-30
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2042-11-30
AI Technical Summary
In the prior art, silica aerogel composites have problems such as uneven impregnation during the preparation process, which affects their thermal insulation performance. The hydrophobic modification process is complex and incomplete, making it difficult to achieve uniform modification.
The liquid-conducting mesh layer and the circulating pump are used to circulate the liquid to improve the reaction efficiency of the hydrophobic modified liquid and the wet gel. By circulating the modified liquid through the circulating pump, the hydrophobic modified liquid is evenly impregnated and the modification process is reduced. time and waste volume.
Significantly improves the use efficiency of hydrophobic modification liquid, reduces the amount of hydrophobic modification liquid and solvent, reduces the amount of waste liquid, improves the thermal insulation performance and hydrophobicity of silica airgel composite materials, and simplifies the production process , reducing costs.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of hydrophobic modified aerogel composite materials, and in particular to a hydrophobic aerogel composite coil and a preparation method thereof. Background Art
[0002] Aerogel is an amorphous solid material with a nanoporous network structure. It is currently receiving widespread attention and application in the fields of thermal protection and new energy vehicles.
[0003] Since pure aerogel has low mechanical strength, it needs to be combined with fibers to form aerogel composite materials for use. The fiber materials used for aerogel composites are also generally referred to as reinforcing fibers or reinforcing fiber materials, and their products include fiber felts or fiber mats.
[0004] When preparing aerogel composite materials, aerogel precursor sol can be used to impregnate reinforcing fiber materials, and then aged and dried to obtain aerogel composite materials. The impregnation methods of aerogel precursor sol include flat folding method, vacuum impregnation method and whole roll normal pressure impregnation method. Among them, the vacuum impregnation method is more complicated to operate, and the flat folding method requires a large container and a large amount of precursor sol. Although the whole roll normal pressure impregnation method can use less precursor sol, it often has problems such as uneven impregnation, which affects the thermal insulation and other properties of the aerogel composite material.
[0005] Silica aerogel composite material is an aerogel composite material that has been studied relatively in depth and applied relatively maturely. It has the characteristics of low density, large specific surface area, high porosity and low thermal conductivity. It is a composite material with relatively good comprehensive thermal insulation performance. The preparation process of silica composite aerogel includes a silicon source hydrolysis reaction. Since a large number of silanol groups are produced during the hydrolysis process, these silanol groups often cannot be completely cross-linked during the gelation process. The residual silanol groups make the silica aerogel have a relatively prominent hydrophilicity and easily absorb moisture from the air. Moreover, aerogel has a rich porous structure and is also easy to absorb moisture from the air. The absorbed and adsorbed moisture affects the thermal insulation performance of the aerogel composite material, so the aerogel composite material needs to be hydrophobized.
[0006] Hydrophobic treatment can be divided into surface post-treatment method and in-situ method. The former uses hydrophobic elimination of hydroxyl groups present in the gel, and the latter adds a hydrophobic reagent containing a hydrophobic group to the sol-gel system to directly form a hydrophobic gel through the sol-gel process. Hydrophobic treatment can also be divided according to the treatment time point relative to drying, and is divided into modification before drying, modification after drying, and modification during drying. In the prior art, whether it is modification before drying or modification after drying, or modification during drying, there are still some problems. For example, modification after drying is easy to damage the aerogel structure, resulting in reduced thermal insulation performance, and there is a problem of incomplete modification effect. Modification during drying has complex modification process operation, high requirements for temperature and pressure, and relatively large safety hazards. Modification before drying is not easy to control, especially when the whole roll dipping method is used to impregnate the modification liquid, it is often difficult to achieve uniform modification.
[0007] Therefore, how to achieve uniform impregnation of the hydrophobic modification liquid to obtain a fully modified silica aerogel composite material is a major technical problem that urgently needs to be solved in the art. Summary of the invention
[0008] In view of one or more of the above technical problems in the prior art, the present invention provides a method for preparing a hydrophobic aerogel composite coil in a first aspect, the method comprising the following steps:
[0009] (1) impregnating a substrate coil with a precursor sol solution and aging the coil to obtain a wet gel composite coil;
[0010] (2) unfolding the wet gel composite coil and laying a liquid-conducting mesh layer on the unfolded wet gel composite coil to obtain a multi-layer coil;
[0011] (3) rolling up the multi-layer coil and impregnating it with a hydrophobic modification liquid to obtain a hydrophobic impregnated coil;
[0012] (4) Drying the hydrophobic impregnated coil to obtain a hydrophobic aerogel composite coil.
[0013] In some preferred embodiments, the precursor sol solution comprises a silicon source, ethanol, water and a catalyst.
[0014] In other preferred embodiments, the precursor sol solution contains a catalytic amount of a catalyst, and the mass ratio of the silicon source, ethanol and water therein is 1:(1-10):(0.1-0.5), for example 1:(2, 3, 4, 5, 6, 7, 8 or 9):(0.2, 0.3 or 0.4).
[0015] In some preferred embodiments, the silicon source may be an organic silicon source. In addition, preferably, the silicon source is selected from one or more of orthosilicic acid, methyl silicate, ethyl silicate, propyl silicate, and butyl silicate.
[0016] In some preferred embodiments, the catalyst is one or more selected from ammonia water, ammonium fluoride and hydrochloric acid. Preferably, the catalyst is a combination of ammonia water and ammonium fluoride, so that the gelation process can be better controlled and the gelation effect is better.
[0017] In a preferred embodiment, the silicon source is orthosilicic acid, aqueous ammonia is used as a catalyst, and the modification time is no more than 10 hours, such as 5 to 8 hours.
[0018] In some preferred embodiments, the substrate coil is selected from one or more of glass fiber needle felt, glass fiber surface felt, pre-oxidized fiber needle felt, ceramic fiber felt and organic open-cell structure foam. More preferably, the organic open-cell structure foam is melamine foam and / or polyurethane foam.
[0019] In some preferred embodiments, the aging is normal temperature and pressure aging or heating aging; preferably, the temperature of the heating aging is 40 to 60°C, such as 45 to 55°C (such as 50°C).
[0020] In a preferred embodiment, the silicon source is ethyl silicate, and aqueous ammonia is used as a catalyst, and the aging is performed at a temperature ranging from 40 to 50° C. for 2 to 4 hours.
[0021] In some preferred embodiments, the thickness of the liquid-conducting mesh layer is not less than 5%, preferably not less than 15%, of the thickness of the base coil. Further preferably, the thickness of the liquid-conducting mesh layer is 0.1 mm to 5.0 mm (e.g., 0.2, 0.5, 1.0, 2.0, 3.0 or 4.0 mm).
[0022] In some preferred embodiments, the liquid-conducting mesh layer is selected from one or more of a nylon mesh layer, a polyester mesh layer, a silk mesh layer, and a cotton mesh layer; preferably, the liquid-conducting mesh layer is one or more of a plain woven mesh layer, a twill woven mesh layer, a satin woven mesh layer, a half-twisted mesh layer, or a fully twisted mesh layer.
[0023] In some preferred embodiments, the solvent of the hydrophobic modification liquid is ethanol.
[0024] In some other preferred or further preferred embodiments, the solute (i.e., modifier) in the hydrophobic modification liquid is selected from one of hexamethyldisilazane, methyltrimethoxysilane, and dimethyldiethoxysilane. It is further preferred that the mass ratio of the solute to the solvent is 1:(10-100) (e.g., 1:20, 1:30, 1:40, 1:50, 1:60, 1:70, 1:80, or 1:90).
[0025] In some preferred embodiments, during the process of using the hydrophobic modification liquid to impregnate the multi-layer coil, the hydrophobic modification liquid is kept flowing. More preferably, the hydrophobic modification liquid circulates through the multi-layer coil to be modified.
[0026] In a second aspect, the present invention provides a hydrophobic aerogel composite coiled material prepared by the method according to the first aspect of the present invention. Preferably, the hydrophobic aerogel composite coiled material has a room temperature thermal conductivity of less than 0.01931 (W / (m·K) and not more than 180Kg / m 3 density, more than 95% water repellency and a 30-minute water immersion rate of no more than 1.5%.
[0027] Compared with the prior art, the present invention improves the reaction efficiency of the hydrophobic modified liquid and the wet gel by providing a liquid-conducting mesh layer and utilizing a circulating pump to circulate the liquid, greatly reduces the modification process time, improves the use efficiency of the hydrophobic modified liquid, reduces the amount of hydrophobic modified liquid and solvent, reduces the amount of waste liquid generated, and alleviates environmental pressure. In particular, in certain preferred embodiments, by selecting a suitable combination of silicon source and catalyst and optimizing the aging method, the silica aerogel composite material can have unexpected performance and shorten the modification time. The silica aerogel composite material prepared by the method of the present invention can significantly reduce the aerogel production time and reduce the production cost, which is particularly beneficial for mass production, thereby realizing the large-scale application of carbon dioxide aerogel composite materials. DETAILED DESCRIPTION
[0028] The detailed description is given below.
[0029] Example 1
[0030] This example prepares a hydrophobic aerogel composite coil, specifically as follows:
[0031] Weigh 77.6 kg of ethyl silicate (silicon content is 40%) and 451.6 kg of ethanol (anhydrous ethanol, 99.5%) respectively, mix them and add them into the reactor, stir for 5 minutes. After stirring evenly, weigh 19.1 kg of deionized water and add it into the reactor, continue stirring for 10 minutes to obtain the first sol glue solution.
[0032] Weigh 7.76 kg of ammonia solution (0.5 mol / L), slowly add it into the first sol solution and stir. After 5 minutes, slowly add 9.7 kg of ammonium fluoride solution (0.5 mol / L) into the mixed solution and continue stirring for 5 minutes to obtain a second sol solution as a precursor sol solution.
[0033] A roll with a thickness of 3.5mm and a density of 95Kg / m 3 The pre-oxidized needle-punched fiber felt with a roll diameter of 0.7m and a width of 1.2m is placed in a gel container, and the second sol glue solution is injected into the container and circulated through the multi-layer coiled material to allow the fiber felt to be fully impregnated and absorbed. The gel is completed about 2 hours after the second sol glue solution circulation is completed, and it is allowed to stand and age for 10 hours to obtain a wet gel composite coiled material.
[0034] Transfer the wet gel composite coil out of the container, unfold it and cover it with a plain woven nylon liquid-conducting mesh layer with a thickness of 0.8 mm and a width of 1.2 m, and then wind the wet gel composite coil covered with the liquid-conducting mesh layer onto the winding disk. Place the wound wet gel composite coil vertically in the modification tank so that the flow direction of the liquid-conducting mesh layer is consistent with the flow direction of the hydrophobic modifying liquid. Weigh 45 L of dimethyldiethoxysilane and 900 L of ethanol (anhydrous ethanol, 99.5%) respectively and mix them evenly to obtain a hydrophobic modifying liquid, and then inject the hydrophobic modifying liquid into the modification tank. Use a circulating pump to pump the hydrophobic modifying liquid out from the bottom of the modification tank and inject it from the axial center of the wet gel winding disk. The flow rate of the circulating pump is 20 m 3 / h, and the modification cycle is repeated for 22 hours to obtain a hydrophobic impregnated coil. The modified hydrophobic impregnated coil is subjected to CO2 supercritical drying, and after drying for 12 hours, a pre-oxidized silk aerogel felt is obtained as a hydrophobic aerogel composite coil.
[0035] The room temperature thermal conductivity of the pre-oxidized silk aerogel felt prepared in this embodiment is 0.01931 W / (m·K) and the density is 179 Kg / m 3 The water repellency is 98.7%, the 30-minute water immersion rate is 1.3%, the fire retardant grade meets the 94-V0 level, and meets the RoHS directive and REACH regulations.
[0036] Example 2
[0037] The process was carried out in substantially the same manner as in Example 1, except that methyl silicate with an equal silicon content was used instead of the ethyl silicate used in Example 1.
[0038] Example 3
[0039] The process is carried out in substantially the same manner as in Example 1, except that orthosilicic acid with an equal silicon content is used instead of the ethyl silicate used in Example 1.
[0040] Example 4
[0041] The process is carried out in substantially the same manner as in Example 1, except that aqueous ammonia having a molar amount equal to the sum of aqueous ammonia and ammonium fluoride in Example 1 is used as a catalyst.
[0042] Example 5
[0043] The process is carried out in substantially the same manner as in Example 4, except that orthosilicic acid with an equal silicon content is used instead of the ethyl silicate used in Example 4.
[0044] Example 6
[0045] The process was carried out in substantially the same manner as in Example 1, except that the modification time was 5 h.
[0046] Example 7
[0047] The process was carried out in substantially the same manner as in Example 5, except that the modification time was 5 h.
[0048] Table 1. Properties of the silica aerogel composites prepared in various examples.
[0049]
[0050] It can be seen from Table 1 that, except for the relatively insufficient hydrophobicity of Examples 3 and 5, the other Examples all obtained composite materials with sufficient hydrophobic modification. In addition, after testing, the fire retardant grade of the carbon dioxide aerogel composite materials prepared in Examples 1 to 7 all met the 94-V0 grade, and met the RoHS directive and REACH regulations.
[0051] It should be noted that the above-mentioned specific embodiments are exemplary, and those skilled in the art can come up with various solutions inspired by the disclosure of the present invention, and these solutions also belong to the disclosure scope of the present invention and fall within the protection scope of the present invention. Those skilled in the art should understand that the description of the present invention is illustrative and does not constitute a limitation on the claims. The scope of protection of the present invention is defined by the claims and their equivalents. The description of the present invention contains multiple inventive concepts, such as "preferably", "according to a preferred embodiment" or "optionally", which means that the corresponding paragraph discloses an independent concept, and the applicant reserves the right to file a divisional application based on each inventive concept.
Claims
1. A method for preparing a hydrophobic aerogel composite coil, characterized in that: The method comprises the following steps: (1) impregnating the base coil with the precursor sol solution and aging the substrate to obtain a wet gel composite coil; (2) unfolding the wet gel composite coil and laying a liquid-conducting mesh layer on the unfolded wet gel composite coil to obtain a multi-layer coil, wherein the liquid-conducting mesh layer is one or more of a plain woven mesh layer, a twill woven mesh layer, a satin woven mesh layer, a half-twisted mesh layer or a full-twisted mesh layer; (3) rolling up the multi-layer coil and placing it vertically in a modification tank, so that the flow direction of the liquid-conducting mesh layer is consistent with the flow direction of the hydrophobic modifier, and impregnating it with a hydrophobic modifying liquid. During the process of impregnating the multi-layer coil with the hydrophobic modifying liquid, the hydrophobic modifying liquid is kept flowing, and the hydrophobic modifying liquid is pumped out from the bottom of the modification tank by a circulation pump and injected from the axial center of the wet gel winding disk to obtain a hydrophobic impregnated coil; (4) drying the hydrophobic impregnated coil to obtain a hydrophobic aerogel composite coil; The silicon source is methyl silicate or ethyl silicate; The thickness of the liquid-conducting mesh layer is not less than 5% of the thickness of the base coil; the thickness of the liquid-conducting mesh layer is 0.1 mm to 5.0 mm.
2. The method according to claim 1, characterized in that The thickness of the liquid-conducting mesh layer is not less than 15% of the thickness of the base coil.
3. The method according to claim 1, characterized in that The precursor sol solution comprises a silicon source, ethanol, water and a catalyst.
4. The method according to claim 3, characterized in that: The precursor sol solution contains a catalytic amount of a catalyst, and the mass ratio of the silicon source, ethanol and water therein is 1:(1-10):(0.1-0.5).
5. The method according to claim 4, characterized in that: The catalyst is one or more selected from ammonia water, ammonium fluoride and hydrochloric acid.
6. The method according to claim 1, characterized in that: The base coil is selected from one or more of glass fiber needle felt, glass fiber surface felt, pre-oxidized fiber needle felt, ceramic fiber felt and organic open-cell structure foam.
7. The method according to claim 6, characterized in that: The organic open-cell structure foam is melamine foam and / or polyurethane foam.
8. The method according to claim 1, characterized in that The aging is aging at room temperature and pressure or heating aging.
9. The method according to claim 8, characterized in that The temperature of the heat aging is 40 to 60°C.
10. The method according to claim 1, characterized in that The liquid-conducting mesh layer is selected from one or more of a nylon mesh layer, a polyester mesh layer, a silk mesh layer, and a cotton mesh layer.
11. The method according to claim 1, characterized in that: The solvent of the hydrophobic modification liquid is ethanol; and / or the solute in the hydrophobic modification liquid is selected from one of hexamethyldisilazane, methyltrimethoxysilane and dimethyldiethoxysilane.
12. The method according to claim 11, characterized in that: The mass ratio of solute to solvent is 1:(10~100).
13. A hydrophobic aerogel composite coiled material prepared according to the method of any one of claims 1 to 12.
Citation Information
Patent Citations
Fiber-reinforced aerogel felt without large aerogel particles adhering onto its surface and preparation method thereof
CN108689678A
Preparation method of high-temperature-resistant glass fiber composite type silicon dioxide aerogel insulation felt
CN109626955A
Preparation system and method of coiled material type aerogel material
CN115709037A
Aerogel-foam composites
US20090029147A1
KR20220039125A